PEDAGOGICAL FOUNDATIONS FOR ASSESSING WRITTEN WORK USING ARTIFICIAL INTELLIGENCE - Dauletiyarova, Nigora Kenesbaevna (SCIENCE and SOCIETY, 2026)
This article examines the pedagogical and psychometric foundations of assessing writing tasks using artificial intelligence. It explores the benefits and limitations of AI-based assessment systems, focusing on reliability, validity, fairness, and academic integrity. The study emphasizes the importance of combining AI capabilities with human expertise to promote critical thinking, student agency, and effective academic writing.
Keywords: artificial intelligence; writing assessment; automated essay scoring; large language models; psychometric validity; assessment fairness; academic writing; critical thinking; feedback; higher education